2014
DOI: 10.1021/jp502795u
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of Silylene Chemistry in the Decomposition of Monomethylsilane in the Presence of a Heated Metal Filament

Abstract: The gas-phase reaction chemistry of the decomposition of monomethylsilane (MMS) has been studied in the presence of a heated metal filament in a hot-wire chemical vapor deposition (HWCVD) reactor. A 10.5 eV vacuum ultraviolet laser single-photon ionization time-of-flight mass spectrometry was employed in combination with isotope labeling and chemical trapping to examine the mechanistic details in the reaction chemistry. We have demonstrated the dominant involvement of the methylsilylene (HSiCH3) intermediate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…On the other hand, homolytic reactions prevail over molecular eliminations for the initial radical intermediates and the stable molecules. Previous studies suggested that homolytic reactions were more important than molecular eliminations in silenes/silylenes in the HMDS pyrolysis, while this study indicated that both homolytic reactions and molecular eliminations were important.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…On the other hand, homolytic reactions prevail over molecular eliminations for the initial radical intermediates and the stable molecules. Previous studies suggested that homolytic reactions were more important than molecular eliminations in silenes/silylenes in the HMDS pyrolysis, while this study indicated that both homolytic reactions and molecular eliminations were important.…”
Section: Discussionmentioning
confidence: 41%
“…The radical reactions are common in thermal decomposition processes. The competition between the radical reactions and the silene/silylene reactions has been discussed in a series of studies on thermal decomposition of methyl-substituted silanes in the hot wire CVD process. It has been demonstrated that the radical reactions take over the silene/silylene reactions gradually with increasing number of methyl substitutions. On the other hand, the silene/silylene reactions become more important with the increase of the number of Si–H bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at m/z 66, 68, 70, 78, 80, 82, and 84 originate from the secondary reaction products of BTD decomposition. 27,40 When compared to the filament-on mass spectra of DSCB in Figure 3, all of the high-mass-product peaks from DSCB including the main ones at m/z 102, 118, 132, and 174 have been significantly suppressed, to an extent that is greater than the effect of BTD addition on the DSCB decomposition efficiency. At the same time, new peaks at m/z 98, 112, and 140 have appeared.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…For MMS, a 4% mixture was used instead of a 1% MMS−He sample due to the fact that the intensities of the peaks were extremely weak when the 1% mixture was used. From our previous study on the gasphase chemistry of MMS, 32 it was found that the major products were 1,2-dimethyldisilane (DMDS) (m/z 90) and 1,3-disilacyclobutane (DSCB) (m/z 88). These products were found to be formed from methylsilylene insertion and methylsilylene dimerization reactions, respectively.…”
Section: Effect Of Source Gas Pressure On Mms Gas-phase Chemistrymentioning
confidence: 99%
“…The lack of hydrocarbon molecules with increasing pressure of MMS is probably due to the fact that free radicals do not participate in the gas-phase chemistry when using MMS, despite the fact that free radicals were detected from the study of the primary decomposition of MMS on the tantalum filament. 32,33 To support the conclusion that the dominant chemistry with MMS is not affected during secondary gas-phase reactions due to the absence of small hydrocarbons produced, experiments of MMS with the addition of ethene were conducted. These experiments will give us insights into the effect of the ethene presence on MMS chemistry if it was produced under our experimental conditions.…”
Section: Effect Of Source Gas Pressure On Mms Gas-phase Chemistrymentioning
confidence: 99%